Investigations of quasi‐static indentation properties of 3D printed polyamide/continuous Kevlar/continuous carbon fiber composites. Issue 32 (20th June 2022) - Wang, Kui; Zhu, Wanying; Li, Shixian; Peng, Yong; Ahzi, Said
Abstract: 3D printing technologies are widely used in aerospace, automobile, and other fields due to their rapid manufacture of strong and lightweight products without additional molds and components. However, the relatively low mechanical behaviors of 3D printed composites were due to the weak pristine matrix and the inherent porosity of the fused deposition modeling (FDM) technology. This drawback was compensated by the addition of hybrid continuous fibers for improving the comprehensive and designable characteristics. In addition, the properties of the hybrid composites could be influenced by changing the processing parameters. Therefore, this work aims to study the mechanical properties of designed 3D printed hybrid continuous carbon and Kevlar fibers reinforced polyamide (PA)‐based composites with different fiber layer locations and stacking sequences. The quasi‐static indentation (QSI) tests were conducted to evaluate the mechanical behaviors of the printed composites. The deformation and failure mechanisms of the printed composites were revealed by fractography. Results demonstrated that the printed composites with the middle fiber layer locations showed the highest force value ( F max ) and higher energy absorption capabilities than the printed composites with the fiber layers placed in other locations, which was attributed to the delayed cracking propagation and large delamination, respectively. Abstract : The mechanical properties of 3D printed hybrid continuous fiber reinforced composites.